Optimal Solver for Morley Element Discretization of Biharmonic Equation on Shape-Regular Grids (Journal of Computational Mathematics, 2018)
This paper presents an optimal solver for the Morley element problem for the boundary-value problem of the biharmonic equation by decomposing it into several subproblems and solving these subproblems optimally. The optimality of the proposed method is mathematically proved for general shape-regular grids.
Keywords: Biharmonic equation; Morley element; Optimal solver; Precondition; Exact sequence.